Pengaruh Media Sosial Dan Pengetahuan Pajak Terhadap Niat Patuh Pajak Pada Generasi Z - Wiharyana, Najwa; Nurkhalisah, Hasna; Maolana, Moch Rifky; Harefa, Romana Mutiara; Linawati, Linawati (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of social media and tax knowledge on tax compliance intention among Generation Z. The increasing use of social media and the advancement of tax digitalization position the younger generation as a strategic group in building sustainable tax compliance. This research employs a quantitative approach using a survey method, with data collected through structured questionnaires and analyzed using multiple linear regression. The conceptual framework of this study is grounded in the Theory of Planned Behavior, which emphasizes the roles of attitude, subjective norms, and perceived behavioral control in shaping intention. The results indicate that social media functions as an effective channel for information dissemination and tax socialization, contributing to the formation of positive perceptions toward taxation. Meanwhile, tax knowledge exerts a stronger influence in enhancing tax compliance intention. These findings underscore the importance of integrating tax education with digital media to foster tax awareness and compliance among Generation Z.